Ash and lignin content of two Malaysian bamboo species - Zakaria, Muhammad Khalaf; Mohamod, Muhammad Imran; Razali, Muhamad Zulhilmi; Engku Fakri, Engku Syahmi Arif; Husin, Syuwari (2012)
The percentage of ash and lignin content in the species of bamboo (Bambusa Spp.) was determine from the bamboo species near the Green bamboo (Bambusa blumeana) and yellow bamboo (Phyllostachysa urea). These are accordance the TAPPI standard. In the thesis the ash and lignin contents in the species of bamboo are more different in the result. The lignin contents in green bamboo and the yellow bamboo are 30.54% and 24.61%. The percentage result of ash is 3.6% of green bamboo and 3.2 % of yellow bamboo. For the overall result, we can conclude the higher of the ash content and the lignin content are for the green bamboo (Bambusa blumeana). These values of percentage lignin and ash are in a TAPPI standard.